Race Matters? Examining and Rethinking Race Portrayal in Preclinical Medical Education. (July 2016) - Tsai, Jennifer; Ucik, Laura; Baldwin, Nell; Hasslinger, Christopher; George, Paul
Abstract : Critical examination of "health disparities" is gaining consideration in medical schools across the United States, often as elective curricula that supplement required education. However, there is disconnect between discussions of race and disparities in these curricula and in core science courses. Specifically, required preclinical science lecturers often operationalize race as a biological concept, framing racialized disparities as inherent in bodies. A three- and five-month sampling of lecture slides at the authors' medical school demonstrated that race was almost always presented as a biological risk factor. This presentation of race as an essential component of epidemiology, risk, diagnosis, and treatment without social context is problematic, as a broad body of literature supports that race is not a robust biological category. The authors opine that current preclinical medical curricula inaccurately employ race as a definitive medical category without context, which may perpetuate misunderstanding of race as a bioscientific datum, increase bias among student–doctors, and ultimately contribute to worse patient outcomes. At the authors' institution, students approached the medical school administration with a letter addressing the current use of race, urging reform. The administration was receptive to proposals for further analysis of race in medical education and created a taskforce to examine curricular reform. Curricular changes were made as part of the construction of a longitudinal race-in-medicine curriculum. The authors seek to use their initiatives and this article to spark critical discussion on how to use teaching of race to work against racial inequality in health care.